Comparison of the SARS-CoV-2 Rapid antigen test to the real star Sars-CoV-2 RT PCR kit - Krüttgen, Alexander; Cornelissen, Christian G.; Dreher, Michael; Hornef, Mathias W.; Imöhl, Matthias; Kleines, Michael (Journal of virological methods, 2021)
•The sensitivity and specificity of the new Roche SARS-CoV-2 Rapid Antigen Test was evaluated.•We found a specificity of 96 %.•The sensitivity with samples with a Ct of < 25 was 100 % and gradually decreases to 22.2 % with cycle thresholds > = 35.•The new test might be useful to rapidly identify contagious individuals. There is an ongoing need for reliable antigen assays for timely and easy detection of individuals with acute SARS-CoV-2 infection. Using 75 swabs from patients previously tested positive by SARS-CoV-2 PCR and 75 swabs from patients previously tested negative by SARS-CoV-2 PCR, we investigated the sensitivity and specificity of the SARS-CoV-2 Rapid Antigen Test (Roche). We determined a specificity of 96 %. The assay’s sensitivity with samples with a cycle threshold of < 25, 25 - <30, 30 - <35, and> = 35 was 100 %, 95 %, 44.8 % and 22.2 %, respectively. We conclude that sensitivity and specificity of the antigen assay is inferior to the PCR assay. However, the antigen assay may be a quick and easy to perform alternative for differentiation of individuals contagious for SARS-CoV-2 from non-contagious individuals.